'Working on a rocky shore': Micro-moments of positive affect in academic work. (May 2019) - Gannon, Susanne; Taylor, Carol; Adams, Gill; Donaghue, Helen; Hannam-Swain, Stephanie; Harris-Evans, Jean; Healey, Joan; Moore, Patricia
Abstract: Neoliberal ideologies, marketization and performative regimes associated with recent reforms in universities have exerted considerable pressure on academic working conditions and subjects in recent years. While analysing these pressures is important, it is also productive to consider the ways in which academics engage in moments of resistance by mobilising resources beyond those of critique. This paper therefore focuses on joy and positive affect in the everyday moments of academic life. It utilises the feminist methodology of collective biography to explore ways of making the restricted spaces of our working day more expansive and finding within them unexpected openings for joy. Our analysis of the stories included in this paper traces the mercurial and ambiguous affective atmospheres of academic work. We suggest that joy is founded upon connections with others, that it arises in different academic spaces and that it can lead to revised knowing of ourselves. We argue that the glimpses of joy evident in this paper provoke affective attunement within the everyday, sensitizing us to other fragments of joy and providing strategies to strengthen that resistance. Highlights: Collective biography methodology enables interrogation of scenes of everyday life in neoliberal universities. Affective atmospheres are ambiguous, always in movement, and envelop people, objects and encounters. Joy can be glimpsed through minute gestures, relations and moments – despite conditions that seem oppressive. Collective biography promotes changes in practice in academic labour and relations.